2019
DOI: 10.1007/s40091-019-00242-w
|View full text |Cite
|
Sign up to set email alerts
|

The efficiency of using CFRP as a strengthening technique for reinforced concrete beams subjected to blast loading

Abstract: Some structures may be subjected to blast loading while in service. This may cause damage or failure to the structural elements. This paper examines the performance of reinforced concrete beams using carbon fiber reinforced polymer (CFRP) when subjected to blast loading. The experimental data including damage and deflection were collected from a previous investigation and numerical analysis was then performed using ABAQUS software. Furthermore, the single degree of freedom (SDOF) model was used to complement t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 11 publications
0
27
0
Order By: Relevance
“…Moreover, the behavior of beams was modeled using ABAQUS 6.14 by SIMULIA to validate the experimental results and predict its behavior under different conditions. Future study might include the structural behavior of reinforced concrete beams and slabs including CRT glass waste under different dynamic load conditions such as blast and impact loads [37][38][39][40] to expand the knowledge on material behavior under different loading conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the behavior of beams was modeled using ABAQUS 6.14 by SIMULIA to validate the experimental results and predict its behavior under different conditions. Future study might include the structural behavior of reinforced concrete beams and slabs including CRT glass waste under different dynamic load conditions such as blast and impact loads [37][38][39][40] to expand the knowledge on material behavior under different loading conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The behavior law used is the concrete damaged plasticity (CDP) model that is a criterion reproducing a behaviour very close to the one of the concrete. [31], [32]. In order to model the steel reinforcement behavior, a firm wire rope element integrated into the concrete was used.…”
Section: Materials Propertiesmentioning
confidence: 99%
“…Fiber reinforced polymer (FRP) as externally bonded reinforcement (EBR) has become a mainstream technology over the last decades to retrofit concrete structures and is also applicable to the case of blast loading [1][2][3][4]. Its effectiveness for strengthening against blast loads is of importance to the building sector, as well as to society from a security and safety perspective.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies are reported about the use of carbon fiber reinforced polymer (CFRP) as EBR for strengthening reinforced concrete structures against blast loading, and application examples are mentioned in [4][5][6][7][8] and the lack of understanding on CFRP debonding under blast impulse follows e.g from [9][10][11][12]. J.Ha et al [9] tested nine RC specimens with dimensions of 1 m × 1 m × 0.15 m retrofitted with either CFRP, polyurea (PU) or hybrid CFRP/PU under blast loading.…”
Section: Introductionmentioning
confidence: 99%